Expand your horizons with the diverse and informative answers found on IDNLearn.com. Our experts provide prompt and accurate answers to help you make informed decisions on any topic.

3. Simplify the expression:

[tex]\[ 2 \frac{1}{4} + 1 \frac{1}{2} \times 2 \frac{2}{3} \][/tex]


Sagot :

To solve the expression [tex]\(2 \frac{1}{4} + 1 \frac{1}{2} \times 2 \frac{2}{3}\)[/tex], we'll follow these steps:

1. Convert the mixed numbers to improper fractions:
- [tex]\(2 \frac{1}{4}\)[/tex] can be converted as follows:
- [tex]\(2 \frac{1}{4} = 2 + \frac{1}{4} = \frac{8}{4} + \frac{1}{4} = \frac{9}{4}\)[/tex]
- [tex]\(1 \frac{1}{2}\)[/tex] can be converted as follows:
- [tex]\(1 \frac{1}{2} = 1 + \frac{1}{2} = \frac{2}{2} + \frac{1}{2} = \frac{3}{2}\)[/tex]
- [tex]\(2 \frac{2}{3}\)[/tex] can be converted as follows:
- [tex]\(2 \frac{2}{3} = 2 + \frac{2}{3} = \frac{6}{3} + \frac{2}{3} = \frac{8}{3}\)[/tex]

2. Multiply the second and third fractions:
- [tex]\(\left(\frac{3}{2}\right) \times \left(\frac{8}{3}\right) = \frac{3 \times 8}{2 \times 3} = \frac{24}{6} = 4\)[/tex]

3. Add the first fraction to the multiplication result:
- [tex]\(\frac{9}{4} + 4\)[/tex]

To add these, convert 4 to a fraction with a denominator of 4:
- [tex]\(4 = \frac{16}{4}\)[/tex]
- So, [tex]\(\frac{9}{4} + \frac{16}{4} = \frac{9 + 16}{4} = \frac{25}{4} = 6 \frac{1}{4}\)[/tex]

Therefore, the value of the expression [tex]\(2 \frac{1}{4} + 1 \frac{1}{2} \times 2 \frac{2}{3}\)[/tex] is [tex]\(6 \frac{1}{4}\)[/tex] or 6.25.